Trace elements : their distribution and effects in the environment - Markert, B. A. (Bernd A.); Friese, K. (Trace metals in the environment, 2000)
This volume discusses major areas of primary concern for the understanding of the complexity associated with ecological trace element research. These include sources and fates of trace elements; analytical techniques; and the distribution of trace elements in biota and soil and sediment reservoirs. Case studies, field work and laboratory studies intensively discussed in this volume are useful to enhance our knowledge about processes related to the biological response of trace metal stress under realistic environmental conditions.